Liver dysfunction in children with community-acquired pneumonia: the role of infectious and inflammatory markers - Dudnyk, Veronika; Pasik, Valentyna (Journal of Education, Health and Sport, 2021)
Markers of infectious-inflammatory process were studied by determining the levels of pro-inflammatory cytokines - interleukin (IL) 1 and IL-6 and proteins of the acute phase of inflammation - C-reactive protein (CRP) and fibrinogen in the serum of children with community-acquired pneumonia. It was found that the course of community-acquired pneumonia is accompanied by an increase in serum concentrations of IL-1 and IL-6 in children in parallel with the disease severity. The synthesis of pro-inflammatory cytokines stimulates the production of acute CRP, but reduces the concentration of fibrinogen in the serum of sick children. The revealed connections between the content of the studied cytokines at the systemic level and multidirectional changes in the indicators of the acute phase of inflammation indicate a violation of the liver, where proteins are synthesized in the study. It is shown that with increasing severity of pneumonia, the enzyme activity of aminotransferases - alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in the serum of children increases with a simultaneous decrease in the de Ritis coefficient, indicating "hepatic" genesis. High levels of aminotransferase is closely correlated with the activity of the infectious-inflammatory process, as indicated by the positive correlation between the level of IL-1 and ALT (r = 0.047) and AST (r = 0.111). At the same time, there is a negative correlation between the levels of IL-1, CRP and the activity of aminotransferases in blood serum.